2008
DOI: 10.1021/nl072921e
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Rotationally Twinned InP Nanowire Heterostructures

Abstract: We have developed a technique so that both transmission electron microscopy and microphotoluminescence can be performed on the same semiconductor nanowire over a large range of optical power, thus allowing us to directly correlate structural and optical properties of rotationally twinned zinc blende InP nanowires. We have constructed the energy band diagram of the resulting multiquantum well heterostructure and have performed detailed quantum mechanical calculations of the electron and hole wave functions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
335
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(364 citation statements)
references
References 39 publications
25
335
3
1
Order By: Relevance
“…It has been demonstrated that other factors, like the effect of ZB and WZ fractions along the axis of the wires [8,12] and spontaneous polarization over the valence band [10,15], play crucial role in determining the optical transitions in such systems. The band bending due to induced space charge by spatially separated electrons and holes, typical in type II quantum well, has also been discussed in the literature [12,16]. In polytype NWs inclusion of stacking fault/twinning in the crystal structure, the twin density and periodicity are shown to be reflected in optical transitions in these systems [8,12,17].…”
Section: Introductionmentioning
confidence: 98%
“…It has been demonstrated that other factors, like the effect of ZB and WZ fractions along the axis of the wires [8,12] and spontaneous polarization over the valence band [10,15], play crucial role in determining the optical transitions in such systems. The band bending due to induced space charge by spatially separated electrons and holes, typical in type II quantum well, has also been discussed in the literature [12,16]. In polytype NWs inclusion of stacking fault/twinning in the crystal structure, the twin density and periodicity are shown to be reflected in optical transitions in these systems [8,12,17].…”
Section: Introductionmentioning
confidence: 98%
“…To date, relatively broad spectra have been obtained, which do not elucidate the quantum nature of these structures. 29,30 In this work, we present structural and optical properties of very clean GaAs zinc-blende/wurtzite nanowires heterostructures with different average contents of wurtzite phases exhibiting localized and sharp emission characteristics. Thanks to the use of local spectroscopy and time-resolved techniques such as confocal photoluminescence and cathodoluminescence ͑CL͒, the quantum confined nature of these heterostructures is elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the bulk counterparts, the structure of the NWs can consist of pure phases of zinc-blende or wurtzite, or a mixture of the two phases. [5][6][7][8][9][10][11][12] Three different aspects of the wurtzite crystal structure in materials that in bulk exist only in zinc-blende form have been studied up to date. First, nucleation theories have been developed to investigate the appearance of wurtzite structure as a direction for obtaining pure crystal phases.…”
Section: Introductionmentioning
confidence: 99%